WORKSHOP PEMBUATAN POC (PUPUK ORGANIK CAIR) DENGAN MEDIA LIMBAH RUMAH TANGGA PADA KADER DESA WRINGINPUTIH KECAMATAN BOROBUDUR KABUPATEN MAGELANG - Naryanto, Rizqi Fitri; Syahriar, Fadhila Fauzia; Fauziyah, Nilna; Nugroho, Muhammad Hafidz Akbar; Murniati, Marika; A’ida, Dalila Najwallah; Amrulloh, Muhammad Iqbal Arif; Septavian, Ihza Humam; Fikrianza, Nabila Hasna; Saputra, Dhimas Andy (LPPM IST AKPRIND Yogyakarta, 2023)
Community service activities have been carried out by a team of volunteers from Universitas Negeri Semarang, namely providing training for female cadres and housewives, especially those in Brongsongan and Kiyudan hamlets, Wringinputih village, Magelang district. The training was in the form of making liquid organic fertilizer using leftover vegetables and fruit peels. The content of the material has taken into account the increasing amount of household waste throughout the year and the absence of proper management of household waste. The results of interviews and discussions that have been conducted show evidence that this training is beneficial for cadres and housewives. The results of the interviews showed that the cadres and housewives did not know that the leftover vegetable and fruit peels they threw away could be used to make organic liquid fertilizer. Next, the results of the interviews and discussions showed that the cadres and housewives were interested in making organic fertilizer from leftover vegetable and fruit peels. Positive responses were given by the participants, thus this illustrates that the training on making liquid organic fertilizer using household waste media is very useful.